Sasakawa and maize production increases in Ghana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Farmers in Ghana are producing twice as much maize as they did in 1986 and the price many of them get for their crop hasrisen by nearly 60%. This progress is the result of the adoption of techniques introduced by Sasakawa-Global 2000. Ghanawas the...